Development of Web-Based Application for Analysis and Design of Steam Power Plant System Parameters Using Biomass Fuel - Offianda Kurniawan; Muhamad Yulianto; Mohamad Solahudin; Haris Mawardi; Lalu Muh Fathul Aziz Al Azhari (The University of Lampung, 2025)
The process of physically prototyping a power generation system is time consuming and costly. Adopting the concept of Digital Twin Technology offers a solution to improve the efficiency in prototyping processes. This study aims to develop a web-based application called ThePOCI for thermal analysis of steam power plant systems working with ideal Rankine cycle, and to evaluate the accuracy of the developed application. The ThePOCI thermal system application consisted of two main modules: Steam Power Plant Design and Combustion Analysis. Validation of the Combustion Analysis module revealed the largest calculation errors in the thermal-based model for variables including flue gas temperature (13.08%), temperature of boiler exit working fluid (16.93%), and turbine power (10.49%), yet all fall within the low error range. Validation of the Steam Power Plant Design module produced deviations of ideal and actual operating conditions of 2.22% and 0.88%, respectively, categorized as highly accurate. The validation results confirm that ThePOCI can accurately simulate the physical system of a steam power plant based on the ideal Rankine cycle. System emission calculations indicate potential for further research on the use of Calliandra biomass in Organic Rankine Cycle (ORC)-based steam power plants, identified as the fuel producing the lowest emissions at 3,742.20 kgCO2e/kW.